DAMPAK MEDIA PERMAINAN BALON SOAL JAWAB TERHADAP HASIL BELAJAR IPA DI KELAS III SDN 3 KARANG BONGKOT TAHUN PELAJARAN 2016/2017 - Fifi Fitrianingrum; Sudirman Sudirman; Nurhasanah Nurhasanah (Indonesian Publication Center, 2020)
This study aims to determine whether there is a balloon game media impact on the answer to the learning outcome of science class III SDN 3 Karang Bongkot Lesson 2016/2017. The method of research is a quasi-type experimental design nonequivalent control group design. The population in this study, is all students in SDN 3 Karang Bongkot. The sample of this research is the entire class III SDN 3 Karang Bongkot which amounted to 40 which consists of two classes namely class III A and class III B. Data collection using tests in the form of the objective sheet. The data obtained are quantitative data. Method of data analysis using the technique of analysis one path ANOVA. Before the first ANOVA test did the prerequisite test that is normality and homogeneity. The results showed the mean values of pretest and posttest of experimental class and control class are 48,00 and 44,00 and 78,67 and 59,67 respectively. The data of this research are the normal and homogeneous distribution with 5% significance level, were the result of hypothesis test with ANOVA analysis technique shows that thing > table stable is 37,98> 4,10. In accordance with the criteria of hypothesis testing, that is if Fhitung ? Ftabel then, H0 rejected and Ha accepted so, it can be concluded that there is the impact of balloon game media about the answer to the learning outcome of science class III SDN 3 Karang Bongkot Lesson 2016/2017, third grade students of SDN 3 Karang Bongkot Lesson Year 2016/2017 increased after the application of balloon game media about the answer.